AB0553 Updated systematic review 2016: efficacy and safety of biological therapy compared to synthetic immunosuppressants or placebo in the treatment of uveitis associated with behÇet's disease. (15th June 2017) - Urruticoechea-Arana, A; Cobo-Ibáñez, T; Villaverde, V García; Santos, M Gόmez; Vargas-Osorio, K; Fariñas-Padrόn, L; Díaz-González, F; Calvo-Río, V; Blanco-Alonso, R
Abstract : Background: Systematic treatment used in ocular involvement of Behçet's disease are corticosteroids, synthetic and biological immunosuppressants. The possible irreversible ophthalmological complications make it a priority to know the efficacy of these drugs. Objectives: To analyze the efficacy and safety of biological therapy vs. Cyclosporin A (CsA), azathioprine (AZA), or placebo in reducing the number of uveitis relapses and improving visual prognosis in patients with Behçet. Methods: Systematic search of the literature in MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials from its inception until August 22, 2016. In additional manual search in international conferences and in the references of included studies. Selection criteria: 1) adults with Behçet's disease and uveitis, 2) Biological therapies, 3) placebo or active comparator with CsA or AZA, 4) outcome measures to evaluate efficacy: number of recurrence of uveitis, visual prognosis, cystic macular edema, retinal vasculitis, vitritis, hypopyon and or adverse events. Meta-analyses, systematic reviews, clinical trials, and observational studies of >10 control patients were included. The selection, review and evaluation of the quality of the articles was carried out by 2 independent reviewers. The Oxford scale was used to determine the quality of studies. Results: Of 256 articles, 9 met the inclusion criteria: 3 retrospective observational and 6 randomized clinical trials in 378 patients with Behçet and refractory uveitis to synthetic corticosteroids and/or immunosuppressants. The age range was 9–63 years, with male dominance and a follow-up period of 6–36 months. The different treatments: 3 observational studies compared infliximab (IFX) with CsA and IFX with CsA associated with AZA or methotrexate (MTX) and IFNα2a with AZA associated with CsA; 2 clinical trial (CT) compared adalimumab (ADA) with placebo; 1 CT RTX associated with MTX with ciclofosfamide (CFM) associated with AZA; 1 CT secukinumab (SECUK) with placebo; Another daclizumab (DACL) with placebo and the last pegIFN-α-2b with systemic and/or immunosuppressive corticosteroids. Adverse events were recorded as secondary outcomes in the 9 studies. Conclusions: With variable evidence, IFX appears to be safe and more effective than CsA in reducing short-term uveitis relapse and the number of severe long term complications and retinal vasculitis flares. RTX is similar to CYA associated with AZA in improving short term inflammatory activity. ADA is more effective than placebo as a corticosteroid sparing, achieving early and sustained control in patients with intermediate, posterior, or active uveitis. PegIFNα-2b significantly reduced the dose of corticosteroids, and improved the quality of life. Treatment with IFNα-2a reduces the uveitis/year relapse rate and improves visual acuity. SECUK and DACL, are not effective in reducing uveitis flares but could have an effect on immunosuppressants sparing. The results of this review support the benefit of performing more well-designed comparative studies with IFX, ADA, RTX and IFN-α. Disclosure of Interest: None declared